Technological study on the Gravity Processing of Manganese Ore - Ts, Zagarzusem; D, Baasanjav; N, Sugir-Erdene; B, Orgilbayar; S, Sukhbat; Ts, Soyolmaa; B, Unursaikhan; L, Jargalsaikhan; E, Otgonjargal (Bulletin of the Institute of Chemistry and Chemical Technology, 2019)
This study investigated the effectiveness of the gravity beneficiation method based on gravitation and centrifugal forces for manganese ore. Manganese ores from Unagad deposit, samples powders were analyzed for their element and mineralogical composition using inductively coupled plasma mass spectrometry (ICP-MS) and X-ray diffractometer (XRD). Mineralogy and petrographic analysis are presented the mineralogical compositions are hydro goethite, manganese minerals and magnetite, the gangue minerals are quartz, albite, orthoclase, microcline in manganese ore. Manganese mineral occurs white, improper shape particles, weak grained-aggregates associated in gangue minerals. The most important minerals consist of manganese minerals are hausmannite, pyrolusite, rhodochrosite, and manganosite. The composite of feed containing 17.31 % Mn and 36.3 % SiO2 was produced by a centrifugal concentrator in combination with the shaking table. In the experiment, a concentrate assaying 41.37% Mn was obtained from this composite with 11.9 % yields. In the next experiment, f80=0.074mm particle size feed ore was used in the MGS concentration test. A concentrate containing 38.33 % Mn with 26.57 % yields was produced in this experiment. The results showed that it is possible to obtain concentrate on the gravity processing of manganese ore that economically significant and meet standard requirements. Манганы хүдрийг гравитацийн аргаар баяжуулах технологийн судалгаа Хураангуй: Энэхүү судалгааны ажлаар манганы хүдрийг хүндийн хүч болон төвөөс зугтах хүчний үйлчлэл дээр үндэслэн гравитацийн аргаар баяжуулах туршилт явуулав. Унагад ордын манганы хүдрийн дээжийн элементийн найрлагыг индукцийн холбоост плазмын масс спектрометр (ICP-MS), эрдсийн найрлагыг рентген дифрактометрийн аргаар тодорхойлсон. Минералоги, петрографийн шинжилгээгээр чулуулагт гидрогётит, манганы эрдсүүд, магнетит гэсэн хүдрийн эрдсүүд, кварц, альбит, ортоклаз, микроклин зэрэг хүдрийн бус эрдсүүд тодорхойлогдлоо. Хүдрийн бус эрдэс дотор манганы эрдэс нь цагаан өнгөтэй, зөв бус хэлбэртэй мөхлөгүүд мөн сул шигтгээлэг байдлаар тааралдаж байна. Манганы эрдсүүд нь гаусманит, пиролюзит, родохрозит, манганизит хэлбэрээр агуулагдсан байна. Манганы 17.31%, цахиурын ислийн 36.3% агуулгатай анхдагч хүдрийг төвөөс зугтах хүчний сепаратор болон ширээний хосолсон аргаар баяжуулахад баяжмалын агуулга Mn-41.37%, гарц 11.9% байв. Харин -0.074 мм фракцийн агуулга 80%-тай анхдагч хүдрийг хүндийн хүчний сепаратор (MGS)–аар баяжуулж, 38.33% -ийн манган агуулсан, 26.57% -ийн гарцтай баяжмал гарган авсан. Иймд манганы хүдрийг гравитацийн аргаар баяжуулахад стандартын шаардлага хангасан эдийн засгийн ач холбогдолтой бүтээгдэхүүн гарган авах боломжтойг тогтоов. Түлхүүр үг: Манганы хүдэр, хүндийн хүчний сепаратор, төвөөс зугтах хүчний сепаратор, рентген - дифрактометр.